2019
DOI: 10.1111/mcn.12926
|View full text |Cite
|
Sign up to set email alerts
|

Trends and factors associated with complementary feeding practices in Ethiopia from 2005 to 2016

Abstract: Introducing appropriate complementary feeding at 6 months of age is crucial for the optimal growth and development of an infant. In Ethiopia, however, no previous national‐level studies have examined the trends and associated factors of complementary feeding practices. The aim of this study is to investigate the trends and determinants of complementary feeding practices in Ethiopia from 2005 to 2016. The study was conducted using the Ethiopia Demographic and Health Survey (EDHS) data for 2005 (N = 2,520), 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 46 publications
10
32
3
Order By: Relevance
“…Consistent with studies conducted in China [ 19 ] and Ethiopia [ 39 ], the current study also found that mothers with secondary and post-secondary education had higher odds of adequate minimum acceptable diet. The possible reason might be that education is directly linked to women’s autonomy, changes in traditional beliefs and women’s control over household resources [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with studies conducted in China [ 19 ] and Ethiopia [ 39 ], the current study also found that mothers with secondary and post-secondary education had higher odds of adequate minimum acceptable diet. The possible reason might be that education is directly linked to women’s autonomy, changes in traditional beliefs and women’s control over household resources [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…The TDHS categorized the household wealth index into lowest, second, middle, fourth and highest. For this study, the household wealth index was re-classified as 'poor', 'middle' or 'rich', consistent with previously published studies [47][48][49]. In those studies, the bottom 40% of the households were referred to as the poor households, the next 40% as the middle-level households and the top 20% as the rich households.…”
Section: Study Factors Influencing the Utilization Of Ancmentioning
confidence: 83%
“…The potential confounders were selected based on previously published studies [10,13,15,26,34,35] and data availability. Potential confounding factors were broadly classified into socioeconomic, demographic and behavioural, health service and community-level factors.…”
Section: Potential Confoundersmentioning
confidence: 99%